The Influence of Product Quality, Price, and After-Sales Service on the Purchase Decision of Honda Matic Motorcycle: Case Study on Students of the Faculty of Economics and Business, Makassar State University - Ahmad Maulana Putra; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin; Amiruddin Tawe; Muh. Ichwan Musa (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of product quality, price, and after-sales service on purchasing decisions for Honda brand Matic Motorbikes individually and simultaneously. The sample used was 100 students of the Faculty of Economics and Business who had been selected based on predetermined criteria. Data collection techniques were carried out by questionnaire and literature study. The data analysis technique consists of validity test, reliability test, classical assumption test which consists of normality test, multicollinearity test, and heteroscedasticity test, multiple linear analysis test, hypothesis testing, determinant coefficient test. All independent variables have a correlation that is in the same direction as the dependent variable (purchase decision). The most dominant variable influencing purchasing decisions is the product quality variable. Which means that the dependent variable purchasing decisions can be explained by variables consisting of product quality, price, and after-sales service, the rest is explained by other variables that are not examined.